A Markowitz mean-variance analysis of hedge fund investments for multi-asset class portfolio holders in South Africa - Naidoo, Lushan (Research of GSB, 2018)
This research aims to provide insight into the hedge fund industry in South Africa. The focus is on retirement funds and the use of hedge funds in a multi-asset class portfolio. Diversification is an important tool for portfolio managers who make use of correlation to achieve higher risk-adjusted returns for investors. As such this paper tests whether higher risk-adjusted returns can be achieved in well diversified multi-asset class portfolios if hedge funds are included. To test for the optimal risk-adjusted returns that can be achieved, mean-variance, mean-semi variance and Omega portfolios were created. The results suggest that portfolios that include hedge fund investments outperformed those that exclude it using mean-variance, mean-semi variance and Omega analysis. Furthermore it was found that portfolios that included Pure Hedge Funds outperformed those that included Fund of Hedge Funds. The evidence suggests that hedge fund investments should be included in a well-diversified South African multi-asset class portfolio, with Pure Hedge Funds being preferred to Fund of Hedge Funds.